Financial Planning And Control In Improving Operational Efficiency - Pratama, Enjel; Susena , Karona Cahya (Utami Publisher, 2025)
This study aims to analyze the role of financial planning and control in improving the operational efficiency of companies. Good financial planning allows companies to allocate resources optimally, project funding needs, and anticipate financial risks. Meanwhile, financial control functions as an evaluation tool to ensure that financial realization is in line with the established plan. The research method used is a case study on a manufacturing company with a qualitative and quantitative approach. Data were collected through observation, interviews, and analysis of financial statements for the past three years. The results of the study indicate that companies that implement an integrated financial planning and control system are able to increase operational efficiency by up to 20%, marked by reduced operational costs and increased productivity. These findings underline the importance of structured financial management practices in supporting the achievement of the company's operational goals in a sustainable manner.